The experiences of unprofessionalism among students in dental education: a qualitative study - Fatemeh Keshmiri (BMC Medical Education)
Abstract Aim The present study aimed to explore the unprofessional behavior of educators, senior students, and peers in the education process of dental and oral health services. Method This qualitative study employed a conventional content analysis approach. The undergraduate students (n = 21) were recruited to participate in the study through purposive sampling. Data were collected through in-depth semi-structured interviews. The qualitative data was analyzed using a five-step conventional content analysis method, as delineated by Graneheim and Lundman. The process involved five steps, including identifying meaning units, condensing them, assigning codes, establishing categories and subcategories, and identifying overarching themes. Results The students’ experiences were explored in a theme “formation of unprofessional subcultures” that includes categories of “multifaceted disrespect”, “dishonesty in professional responsibility”, and “neglecting the professional accountability.” Conclusion According to the findings, educators and students exhibited unprofessional conduct in accountability, respect, and honesty. The results indicate that disrespectful behavior, dishonesty, irresponsibility, and a lack of accountability have become normal within the dental education system. This normalization occurs through the hidden curriculum, which inadvertently educates students on these unprofessional behaviors alongside the formal curriculum. The subcultures of unprofessionalism were explained as a trigger that significantly influences students’ professional development and future behaviors in the dental field.